Depressive symptoms and associated factors among pregnant women attending antenatal care at Comprehensive Specialized Hospitals in Northwest Ethiopia, 2022: an institution-based cross-sectional study - Takelle, Girmaw Medfu; Nakie, Girum; Rtbey, Gidey; Melkam, Mamaru (Frontiers in Psychiatry, 2023)
Background Depression during pregnancy has a significant impact on public health as it can adversely affect both the mother's and the child's health. These can have devastating effects on the mother, the unborn child, and the entire family. Objective This study aimed to determine the prevalence of depressive symptoms and associated factors among pregnant women in Ethiopia. Method An institutional-based cross-sectional study was conducted among pregnant women attending antenatal care services at comprehensive specialized hospitals in Northwest Ethiopia from May to June 2022. Measurement The desired data were collected through face-to-face interview techniques by using validated questionnaires such as the Edinburgh Postnatal Depression Scale, the Oslo-3 social support scale, and the Abuse Assessment Screen tools. The data were analyzed by using SPSS Version 25. Logistic regression analysis was used to identify factors associated with antenatal depressive symptoms. Variables having a p-value of <0.2 in the bivariate analysis were entered into the multivariable logistic regression. A p-value of <0.05 was considered statistically significant, at 95% CI. Results This study revealed that 91 (19.2%) pregnant women screened positive for depressive symptoms. According to multivariable logistic regression, living in rural areas (adjusted odds ratio (AOR) = 2.58, 95% CI: 1.267, 5.256), being in the second or third trimesters of gestational phase (AOR = 4.40, 95% CI: 1.949, 9.966 and AOR = 5.42, 95% CI: 2.438, 12.028, respectively), having a history of alcohol use (AOR = 2.41, 95% CI: 1.099, 5.260), having moderate or poor social support (AOR = 2.55, 95% CI: 1.220, 5.338 and AOR = 2.41, 95% CI: 1.106, 5.268), and having a history of intimate partner violence (AOR = 2.67, 95% CI: 1.416, 5.016) were the factors significantly associated with depressive symptoms at a p-value of ≤ 0.05. Conclusion and recommendation The prevalence of depressive symptoms among pregnant women was high. Living in rural areas, second and third trimesters, use of alcohol, having moderate to poor social support, and having a history of intimate partner violence were variables significantly associated with depressive symptoms during pregnancy.